Composing literacy: Exploring how musical aptitude explains technical reading abilities - Aintila, Johanna (My University, 2020)
Several studies have indicated a connection between musical skills and reading-related abilities. However, the underlying reasons to the connection have been unclear. I studied whether subskills within musical aptitude can explain the relationship between music and reading in 8–11-year-old children (N = 66). The children were tested for musical aptitude subskills: pitch discrimination, temporal discrimination, and tonal memory. The focus lay on technical reading abilities, namely performance in reading fluency and sentence comprehension in the Finnish primary school reading test. Linear regression models were used to assess whether the subskills, both together and separately, account for the variance in reading performance. The combination of musical aptitude subskills was related to technical reading abilities. Independently of other subskills, tonal memory explained both reading fluency and sentence comprehension while pitch discrimination explained only reading fluency. The findings support the hypothesis that musical aptitude and reading-related abilities share common mechanisms, such as pitch perception. More extensive research on how musical aptitude and reading are related is needed. Information about the underlying mechanisms in them could be used to create music interventions to support reading acquisition.
Keywords: music, musical aptitude, reading, reading fluency, sentence comprehension